KANDUNGAN VITAMIN C, KUALITAS SENSORIS, DAN TINGKAT KESUKAAN PADA ES KRIM BUAH NAGA (HYLOCEREUS POLYRHIZUS) - Azizah, Alfina; Mahalia, Lamia Diang (Universitas Negeri Medan, 2023)
Dragon fruit is cultivated in Indonesia and has a high vitamin C content.The consumption of dragon fruit is still lacking and the use into processed food products is still limited.The objective of this study was to analyze of vitamin C content, sensory quality, and level of preference of dragon fruit ice cream.This is experimental research with a Completely Randomized Design. The addition of dragon fruit, in formula P1 as much as 350 g, formula P2 400 g, formula P3 450 g, formula P4 500 g.The data were processed and analyzed descriptively. Based on the results of the organoleptic test, it was obtained that P1 formula was the most chosen with a very distinctive aroma and very soft texture, P3 formula was the most chosen with a sweet taste, and P2 formula was the most chosen with a purple color. The results of the dragon fruit ice cream preference test showed that the majority of panelists liked the aroma, taste, texture of P3 formula, and the color of P4 formula. Dragon fruit ice cream has a vitamin C content of 33.7-47.8 mg/100. It can be conclude that the majority of the panelists liked the aroma, taste, texture of the P3 formula, and the color of the P4 formula. Dragon fruit ice cream contained Vitamin C met the standard consumption requirement/day (30-60 mg/day). It is recommended to use the P4 formula to make dragon fruit ice creamKeywords—ice cream formula, organoleptic test, preference test